2015
DOI: 10.7547/13-122.1
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Custom Foot Orthoses for the Treatment of Plantar Heel Pain

Abstract: The CFO group demonstrated 5.6-fold greater improvements in spontaneous physical activity versus the PFO and sham groups. All three groups improved in morning pain after treatment that included standardized athletic shoes, stretching, and ice. The CFO changes may have been moderated by decreased stretching and ice use after 3 months. These findings suggest that more objective measures, such as spontaneous physical activity improvement, may be more sensitive and specific for detecting improved weightbearing fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 47 publications
3
60
0
Order By: Relevance
“…Three studies reported on function at short term and pooled results from two studies showed no significant difference ((SMD −0.27 (95%CI −0.58 to 0.04)), I 2 0%) between sham and custom-made orthoses(online supplementary file 7). Similar results were found in the study that could not be pooled for short-term function 21. One study reported on midterm function and found no difference between both interventions 19.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Three studies reported on function at short term and pooled results from two studies showed no significant difference ((SMD −0.27 (95%CI −0.58 to 0.04)), I 2 0%) between sham and custom-made orthoses(online supplementary file 7). Similar results were found in the study that could not be pooled for short-term function 21. One study reported on midterm function and found no difference between both interventions 19.…”
Section: Resultssupporting
confidence: 83%
“…Landorf et al 15 showed a significantly larger improvement in function at short term for prefabricated orthoses compared with sham orthoses (MD 8.40 (scale 0–100) (95% CI 1.00 to 15.80)), but no difference was seen at long term. Wrobel et al 21 found no significant difference between the two interventions for the Foot Function Index (FFI) at short term21 (online supplementary file 3). …”
Section: Resultsmentioning
confidence: 99%
“…Data were unable to be obtained from one trial40 after contacting the authors and were excluded from the meta-analysis. Data for ‘first step’ pain in the short term were available from a single trial,27 and no trials reported ‘first step’ pain in the longer term.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the use of custom foot orthoses can effectively reduce foot pain and increase spontaneous physical activity [14], potentially increasing older adults’ adherence and acceptability to foot orthoses in their free-living environment. In the past, Yalla et al [15] conducted a proof-of-concept study and showed that wearing bilateral AFO with a custom-made footplate can immediately improve the postural stability of older adults during balance assessments performed in a laboratory environment, but the benefits of the daily use of this custom-made AFO were not evaluated [15].…”
Section: Introductionmentioning
confidence: 99%